2022
DOI: 10.3390/cancers14184504
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Leukemia-Derived Exosome Enrichment and Co-isolated dsDNA Sequencing in Acute Myeloid Leukemia Patients: A Proof of Concept for New Leukemia Biomarkers Detection

Abstract: Exosomes are extracellular vesicles playing a pivotal role in the intercellular communication. They shuttle different cargoes, including nucleic acids from their cell of origin. For this reason, they have been studied as carriers of tumor markers in different liquid biopsy approaches, in particular for solid tumors. Few data are available concerning exosomes as markers of myeloid neoplasia. To better understand their real potential and the best approach to investigate leukemic exosomes, we present the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Therefore, the use of cfDNA may increase the sensitivity of peripheral blood for detection of MRD. Studies have shown that the use of extracellular vesicles obtained from PB samples can be used for the detection of prognostic and follow-up biomarkers in AML ( 33 38 ). In general, bone marrow was studied because it increases sensitivity by at least one logarithm versus peripheral blood for MRD evaluation in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of cfDNA may increase the sensitivity of peripheral blood for detection of MRD. Studies have shown that the use of extracellular vesicles obtained from PB samples can be used for the detection of prognostic and follow-up biomarkers in AML ( 33 38 ). In general, bone marrow was studied because it increases sensitivity by at least one logarithm versus peripheral blood for MRD evaluation in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma exosomal lncRNAs are potential cell-free indicators for the diagnosis and therapeutic monitoring of AML and offer novel and cutting-edge concepts for the liquid biopsy of hematologic cancers (98). Bernardi et al first used the commercially available CE-IVD-based kits for exosome-enrichment methods to investigate leukemic sources and exosomal dsDNA target resequencing for adult AML marker detection; they performed next-generation sequencing analysis of exosome-derived dsDNA isolated from 14 adult patients with AML and identified the optimal amount of exosomal dsDNA as a potential AML biomarker for liquid biopsies; they found exosomal dsDNA can be developed as a tool that can facilitate the monitoring of AML progression and the early diagnosis of relapse after allogeneic hematopoietic stem cell transplantation (99). In summary, exosomes may offer a novel perspective on AML diagnosis and treatment response (Table 2).…”
Section: Application Of Exosomes In the Diagnosis And Prognosis Of Amlmentioning
confidence: 99%
“…[50][51][52] Last but not least, the application of dPCR resulted able to performing a precise, sensitive, and accurate quantification of BCR::ABL1 transcripts shuttled by circulating extracellular vesicles, 53,54 similar to what was observed in another type of leukemia. [55][56][57] Considering these encouraging results, it is not surprising that new commercial assays have become available for BCR::ABL1 transcript detection by dPCR 58 and that coordinated multicentric studies are optimizing and standardizing CML MRD monitoring by dPCR. 59,60 These data are constantly confirmed by new evidence and altogether stress the utility of moving to dPCR for minimal residual disease (MRD) monitoring in CML patients, in particular in subjects presenting low levels of BCR::ABL1 transcript and potentially eligible for stopping TKI therapy.…”
Section: Toward the Identification Of The Best Candidates For Tfrmentioning
confidence: 99%
“… 50 52 Last but not least, the application of dPCR resulted able to performing a precise, sensitive, and accurate quantification of BCR::ABL1 transcripts shuttled by circulating extracellular vesicles, 53 , 54 similar to what was observed in another type of leukemia. 55 57 …”
Section: Toward the Identification Of The Best Candidates For Tfrmentioning
confidence: 99%